Analysis of Manyas Lake Surface Area and Shoreline Change Over Various Periods with DSAS Tool - UZUN, SULTAN MURAT (My University, 2024)
In this study, the shoreline and lake surface area changes of Lake Manyas were analysed by using Geographical Information Systems (GIS) and Remote Sensing (RS) techniques for long term (1980-2020) and annual (2022) with DSAS tool. In the study, a formula was created using NDWI, MDWI, WRI water indices and NDVI, RVI, NDMI, GCI vegetation indices over Landsat satellite images of 1980, 1985, 1990, 1995, 2000, 2000, 2005, 2005, 2010, 2015, 2020 and all months of 2022, and shoreline extraction was performed. Then, shoreline and lake surface area change were analysed over different periods with NSM, EPR, SCE, LRR statistics in DSAS tool. According to the results of the analyses, the average shoreline changes between 1980 and 2020 was 139 m according to NSM statistics, 3,5 m/year according to EPR, 243.1 m according to SCE and 3.4 m/year according to LRR. While the shoreline extended a maximum of 1599 m, the minimum value was -403 m. From 1980 to 2020, 5.85 km2 coastal accumulation, 1.03 km2 coastal erosion and 146.5 km2 permanent lake surface area data were determined on the surface area and shores of Lake Manyas. According to the monthly data of Lake Manyas for 2022, the shoreline is advancing by 18 m on average. Due to the natural dynamic process and the productive structure of the wetland system, the lake surface area reaches its widest size in April with 149.01 km2 and its narrowest area is 146.05 km2 in August. On the southern shores of Lake Manyas, reedbed development and coastal accumulation are intensely experienced with the progression of the Manyas Stream delta, while coastal erosion is observed on the northern shores.

Bu çalışmada Manyas Gölü’nün kıyı çizgisi ve göl yüzey alanı değişimi, Coğrafi Bilgi Sistemleri (CBS) ve Uzaktan Algılama (UA) teknikleri kullanılarak, uzun dönemli (1980-2020) ve yıllık (2022) olarak DSAS aracı ile analiz edilmiştir. Çalışmada 1980, 1985, 1990, 1995, 2000, 2005, 2010, 2015, 2020 yıllarına ait ve 2022 yılının bütün aylarına ait Landsat uydu görüntüleri üzerinden NDWI, MDWI, WRI su indeksleri ve NDVI, RVI, NDMI, GCI bitki indeksleri kullanılarak formül oluşturulmuş, kıyı çizgisi çıkarımı yapılmıştır. Daha sonra DSAS aracındaki NSM, EPR, SCE, LRR istatistikleri ile kıyı çizgisi ve göl yüzey alanı değişimi farklı periyotlar üzerinden analiz edilmiştir. Analiz bulgularına göre 1980-2020 yılları arasında ortalama kıyı çizgisi değişimi NSM istatistiğinde 139 m, EPR’ye göre 3,5 m/yıl, SCE’ye göre 243,1 m ve LRR’ye göre 3,4 m/yıl olarak saptanmıştır. Kıyı çizgisi maksimum 1599 m ilerken minimum değer olarak -403 m gerilemiştir. Manyas Gölü yüzey alanı ve kıyılarında 1980’den 2020 yılına kadar 5,85 km2 kıyı birikimi, 1,03 km2 kıyı erozyonu ve 146,5 km2 daimî göl yüzey alanı verisi tespit edilmiştir. Manyas Gölü 2022 yılı aylık verilerine göre kıyı çizgisi ortalama 18 m ilerlemektedir. Doğal dinamik süreç ve sulak alan sisteminin üretken yapısı nedeniyle göl yüzey alanı en geniş boyutuna nisan ayında 149,01 km2 ile ulaşmakta, ağustos ayında ise en dar alanı 146,05 km2 olarak görülmektedir. Manyas Gölü güney kıyılarında sazlık alan gelişimi ve Manyas Çayı deltasının ilerlemesi ile kıyı birikimi yoğun şekilde yaşanırken, kuzey kıyılarda kıyı aşınımı gözlemlenmiştir.
Manyas Gölü Yüzey Alanı ve Kıyı Çizgisi Değişiminin Çeşitli Periyotlar Üzerinden DSAS Aracı ile Analizi
Keywords: DSAS; Manyas Gölü; Kıyı Çizgisi Değişimi; Uzaktan Algılama; CBS; Manyas Lake; Shoreline Change; Remote Sensing; GIS